2020
DOI: 10.1515/comp-2020-0153
|View full text |Cite
|
Sign up to set email alerts
|

On the Effectiveness of Self-Training in MOOC Dropout Prediction

Abstract: Massive open online courses (MOOCs) have gained enormous popularity in recent years and have attracted learners worldwide. However, MOOCs face a crucial challenge in the high dropout rate, which varies between 91%-93%. An interplay between different learning analytics strategies and MOOCs have emerged as a research area to reduce dropout rate. Most existing studies use click-stream features as engagement patterns to predict at-risk students. However, this study uses a combination of click-stream features and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 38 publications
(54 reference statements)
2
19
0
1
Order By: Relevance
“…Alraimi, Zo, and Ciganek (2015) pointed out that retention rates are on average less than 10 percent and the completion rate is extremely low. Dropout rates of MOOCs are between 91 percent and 93 percent (Goel & Goyal, 2020). A high dropout rate leads to an average completion rate which is less than 13 percent (Krause, Mogalle, Pohl, & Williams, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Alraimi, Zo, and Ciganek (2015) pointed out that retention rates are on average less than 10 percent and the completion rate is extremely low. Dropout rates of MOOCs are between 91 percent and 93 percent (Goel & Goyal, 2020). A high dropout rate leads to an average completion rate which is less than 13 percent (Krause, Mogalle, Pohl, & Williams, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…As such, we employed the SMOTE technique on student learning data each week to make sure samples in the two target classes in the dataset are equal. This is in line with the research of Goel and Goyal (2020). Multiple approaches (i.e., Undersampling, Oversampling, and Hybrid methods) were employed by the authors to balance the different classes in the dataset to ensure that the model could better capture the underlying patterns.…”
Section: Discussionmentioning
confidence: 57%
“…Another research described by Gray and Perkins ( 2019 ) and Chui et al ( 2020 ) identified marginal students who are at-risk of low achievement. Authors in (Adnan et al, 2021 ; Dass et al, 2021 ; Goel & Goyal, 2020 ; Kabathova & Drlik, 2021 ) identified dropout students based on their academic results.…”
Section: Resultsmentioning
confidence: 99%